MITYVAC VACUUM DELIVERY SYSTEM AND THE NEW VACUUM CMI DS OUR EXPERIENCE IN HANDLING IN 100 PREGNANT - Vidal Amat y León, Jorge (2015)
This work corresponds to the experience in managing Mityvac DELIVERY SYSTEM VACUUM and VACUUM new CMI DS presented in a mother-child hospital in Lima, Peru, Rimac district and private patients. Extending our experience to a publication of the year 87. The important significance has had the use in Peru of this instrument has allowed important support in the hard and risky journey of life, that is birth. The Mityvac consists of a vacuum extractor, simple instrument whose dissemination is increasing in hospitals in the United States of America, as in Latin America. Particularly in Peru use it is presented since 1986 by moving to the forceps and vacuum extractor OF MALMSTRONG thereby reducing the risks at delivery. The creation of Mityvac DELIVERY SYSTEM VACUUM due to MEDICAL & SURGICAL COLUMBIA, so many specialists are implementing one of the most important achievements in instrumental obstetrician gynecologist is concerned, in recent years. We believe based on the illustrative experience management, with the Mityvac DELIVERY SYSTEM VACUUM is provided and maximum security is given to the mother and infant in those parts that could present difficulties. We consider: Simple, safe, very effective and being prepared for immediate use with disposable sterile equipment. Its use is the responsibility of specialist based on his experience as a critical evaluation and to indicate the need for application time factor. The Mityvac is ready to increase the expulsive power of the mother and facilitating the natural rotation of the fetal head, shortening the period during vaginal delivery expulsion; and can be also used in cesarean sections.